Identifying Genomic Variations in Monozygotic Twins Discordant for Autism Spectrum Disorder Using Whole-Genome Sequencing - Yan Huang; Yue Zhao; Yue Ren; Ying Yi; Xiaodan Li; Zhaomin Gao; Xiaolei Zhan; Jia Yu; Dong Wang; Shuang Liang; Lijie Wu (Elsevier, 2019)
Autism spectrum disorder (ASD) presents a set of childhood neurodevelopmental disorders with impairments in social communication and restricted, repetitive, and stereotyped patterns of behavior. Here, based on the whole-genome sequencing (WGS) data of three monozygotic twins discordant for ASD, we explored multiple patient-specific genetic variations and prioritized a list of ASD risk genes. Our results identified DVMT (discordant variation in monozygotic twin) observed in at least two twin pairs, including 14,310 SNPs, 2,425 indels, and 16,735 CNVs, referring to a total of 2,174 genes, and 37 of these were covered by all three types of variations. Gene ontology (GO) enrichment analysis of biological processes for 2,174 genes showed that the majority of these genes were related to neurodevelopmental processes. In addition, functional network analysis showed that there was a strong functional relevance between 37 genes covered by all three types of variations. In conclusion, for the first time, we conducted a comprehensive scan of genomic differences between monozygotic twins discordant for ASD, providing researchers with in-depth directions. It may also provide effective strategies for clinical treatment of individuals affected by ASD. Keywords: genomic variations, autism spectrum disorder, monozygotic twins, whole-genome sequencing